Sex differences in the neuroadaptations associated with incubated cocaine-craving: A focus on the dorsomedial prefrontal cortex - Towers, Eleanor Blair; Kilgore, Madison; Bakhti-Suroosh, Anousheh; Pidaparthi, Lasyapriya; Williams, Ivy L.; Abel, Jean M.; Lynch, Wendy J. (Frontiers in Behavioral Neuroscience, 2023)
Women have a shorter course from initial cocaine use to meeting the criteria for cocaine use disorder as compared to men. Preclinical findings similarly indicate that females develop key features of an addiction-like phenotype faster than males, including an enhanced motivation for cocaine and compulsive use, indicating that this phenomenon is biologically based. The goals of this study were to determine whether cocaine-craving, another key feature of addiction, also develops sooner during withdrawal in females than males and to determine whether there are sex differences in the molecular mechanisms associated with its development focusing on markers known to mediate cocaine-craving in males (i.e., dorsomedial prefrontal cortex, dmPFC, expression of brain-derived neurotrophic factor exon-IV, Bdnf-IV, and NMDA receptor subunits, Grin2a, Grin2b, and Grin1). Cocaine-craving was assessed following extended-access cocaine self-administration and 2, 7, or 14 days of withdrawal using an extinction/cue-induced reinstatement procedure. Tissue was obtained from the dmPFC immediately after reinstatement testing and gene expression changes were analyzed using real-time qPCR. In males, cocaine-craving (total extinction and cue-induced reinstatement responding) progressively increased from early to later withdrawal time-points whereas in females, cocaine-craving was already elevated during early withdrawal (after 2 days) and did not further increase at later withdrawal time-points. Levels of cocaine-craving, however, were similar between the sexes. Gene expression changes differed markedly between the sexes such that males showed the expected relapse- and withdrawal-associated changes in Bdnf-IV, Grin2a, Grin2b, and Grin1 expression, but females only showed a modest increase Grin1 expression at the intermediate withdrawal timepoint. These findings indicate that cocaine-craving is similarly expressed in males and females although the time-course for its incubation appears to be accelerated in females; the molecular mechanisms also likely differ in females versus males.